Credit Dispute Resolution through Banking Mediation during Covid-19 Pandemic Situation - Bondan Seno Aji; Made Warka; Evi Kongres (Budapest International Research and Critics University, 2021)
This study aims to find out credit dispute resolution through banking mediation in pandemic situation. This study use qualitative research method. The result shows that Settlement of bank credit problems that arose as a result of the Covid-19 pandemic, namely through deliberations between the bank (creditor) and the debtor. In POJK No.18 / POJK.07 / 2018 concerning Consumer Protection in the Financial Services Sector, it is stipulated that every financial service institution is required to have a work unit and / or function as well as a service and complaint resolution mechanism for consumers. If the dispute resolution at a financial service institution does not reach an agreement, consumers can resolve the dispute through the court or outside the court. Out of court dispute resolution is carried out through arbitration and alternative dispute resolution.